- KINERJA PEGAWAI PEGADAIAN DI UNIT PEGADAIAN CABANG (UPC) PUTUSSIBAU DALAM MEMBERIKAN PELAYANAN KEPADA MASYARAKAT: Kinerja. Pelayanan - Nikodimus, Nikodimus (Universitas Kapuas Sintang, 2025)
This study aims to determine the performance of Pegadaian employees at the Putussibau BranchPawnshop Unit (UPC) in providing services to the public. This research is expected to enrich the body ofresearch on Pegadaian employees' performance at the Putussibau Branch Pawnshop Unit (UPC) inproviding services to the public, and is expected to contribute to the Kapuas Hulu Regency Government inparticular. This study aims to analyze, describe, and explain in depth various aspects related to theproblems and efforts to improve Pegadaian employee service performance at the Putussibau BranchPawnshop Unit (UPC). This study refers to the characteristics of qualitative and descriptive research,meaning that the researcher will conduct in-depth research on various aspects related to service. Severalresearch subjects have been identified as informants or data sources, including the Head of the Office andstaff at the office. The results indicate that the service performance of Pegadaian employees at thePutussibau Branch Pawnshop Unit (UPC) in providing services to the public is quite good, asdemonstrated by the employees' commitment and sincerity in carrying out their duties and functions